The 2013 Curriculum Assistance for the Raudatul Atfal Teachers in Pontang Sub-district, Serang Regency - Huliyah, Muhiyatul (Indonesian Journal of Islamic Early Childhood Education, 2018)
The aim of this community service activity (PKM) was to improve understanding of the  2013 curriculum in Raudatul Atfal (islamic kindergarten) teachers in Pontang sub-district, Serang regency. The method used in this community service activity is Participatory Action Research (PAR). To collect data and analyze it, researchers used sharing, in-depth interviews, and Focus Group Discussions (FGD). This activity was attended by 13 RA, i.e. RA Al-Khairiyah Pontang, RA Al Islamiyah, RA Sultan Agung Tirtayasa, RA Ashabul Maimanah Sidayu, RA Al-Khairiyah Boyongbong, RA Mathla’ul Anwar, RA Al-Khairiyah Domas, RA Al Khairot, RA Hidayatussibyan, RA Ar-Rohmani, RA Al-Amaliya, RA Cahaya Pertiwi Banten, RA Al Khairiyah Kelepian.  After the curriculum 2013 assistance program conducted in RA in Pontang sub-district, there were fundamental changes to the participants, i.e. (1) having knowledge about the 2013 curriculum, (2) being able to apply the innovative and creative 2013 curriculum. (3) a change in the paradigm of the 2013 curriculum which can improve the ability, potency, and development of early childhood in RA Pontang sub-district.